Effects of material heterogeneity on self-rolling of strained membranes. (May 2019) - Chen, Cheng; Song, Pengfei; Meng, Fanchao; Ou, Pengfei; Lan, Guoqiang; Liu, Xinyu; Song, Jun
Abstract: The present work studies the effects of strained membranes. An analytical framework has been established to predict self-rolling curvatures of strained bilayer membranes containing heterogeneous material elements. The accuracy of the framework is validated through molecular dynamics (MD) simulations on the heterogeneous CdTe x S 1 − x /CdTe bilayer system. Moreover, numerical simulations using finite-element modeling (FEM) have been performed to examine the role of heterogeneous elements in the complex helical rolling. It has been demonstrated that both the rolling direction and rollup curvature can be predictively controlled by modulating the material heterogeneity and layer thickness. The present study points to a new pathway towards predictive design and tuning of complex 3D structures based on strained membranes through incorporation of heterogeneous elements.